PERILAKU POLITIK KIAI DI PAMEKASAN - Mohammad Muchlis Sholichin (Karsa: Journal of Social and Islamic Culture)
Abstrac Kiais (muslim sholar) and their pesantren (Islamic boarding school) is character of religious leader. They prove themselves as a non-formal leader in Indonesian society. The influence of Kiai depends on both the sophistication knowledge and power they have. It can be recognized from the achievement of their pesantren.  In the context of modernity dynamic, another impotant role of kiai is as a patron of Islamic group that tries to articulate their interest, due to the fact that they claim themselves as the acknowledger in organizing a relation with the outside. With their superiority, they can influence and control society. Kiai is also a charismatic and respected leader.  They are an ideal figure indicating the high cultural and structural sites in society Kata-kata kunci kiai, politik, kharisma, dan pesantren